Lead fixation mechanism impacts outcome of transvenous lead extraction: data from the European Lead Extraction ConTRolled Registry. Issue 5 (15th October 2021) - Levi, Nir; Bongiorni, Maria Grazia; Rav Acha, Moshe; Tovia-Brodie, Oholi; Kennergren, Charles; Auricchio, Angelo; Maggioni, Aldo Pietro; Rinaldi, Christopher A; Nof, Eyal; Ilan, Michael; Blomstrom-Lundqvist, Carina; Deharo, Jean-Claude; et al.
Abstract: Aims: The aims of this study is to characterize the transvenous lead extraction (TLE) population with active (A) compared with passive fixation (PFix) leads and to compare the safety, efficacy, and ease of extracting active fixation (AFix) compared with PFix right atrial (RA) and right ventricular (RV) leads. Methods and results: The European Lead Extraction ConTRolled Registry (ELECTRa) was analysed. Patients were divided into three groups; those with only AFix, only PFix, and combined Fix leads. Three outcomes were defined. Difficult extraction, complete radiological, and clinical success. Multivariate model was used to analyse the independent effect of Fix mechanism on these outcomes. The study included 2815 patients, 1456 (51.7%) with only AFix leads, 982 (34.9%) with only PFix leads, and 377 (13.4%) with combined Fix leads. Patients with AFix leads were younger with shorter lead dwelling time. Infection was the leading cause for TLE among the combined Fix group with lowest rates among AFix group. No difference in complications rates was noted between patients with only AFix vs. PFix leads. Overall, there were 1689 RA (1046 AFix and 643 PFix) and 2617 RV leads (1441 AFix and 1176 PFix). Multivariate model demonstrated that PFix is independently associated with more difficult extraction for both RA and RV leads, lower radiological success in the RA but has no effect on clinical success. Conclusion: Mechanism of Fix impact the ease of TLE of RA and RV leads and rates of complete radiological success in the RA but not clinical success. These findings should be considered during implantation and TLE procedures.